Effect of environmental factors on performance of jointed concrete pavements. Issue 6 (16th February 2021) - Kim, Dong-Hyuk; Lee, Jun-Hyeok; Moon, Ki-Hoon; Jeong, Jin-Hoon
Abstract : This study investigated the distress conditions of test sections of concrete pavement that have been used for more than the design life of 20 years. The study was performed using data from a highway pavement management system. To determine the effects of distress and environmental factors, weather data were analysed for the test sections. Regression models were developed for five types of distress: longitudinal cracks, asphalt patching, concrete patching, durability cracks and longitudinal spalling. The influence of environmental factors was analysed, such as the days with temperature below zero, number of freeze and thaw cycles, average relative humidity and the amount of de-icing salt consumed. Using these models, the amount of distress was predicted and compared with the actual amount of distress. The predicted amount of distress was similar to the actual amount of distress, indicating that the models were properly developed. Using the results of this study, the distress of aging concrete pavement could be reduced by managing the environmental factors more appropriately.